PELATIHAN DAN EDUKASI SENAM PELVIC ROCKING PADA IBU HAMIL TRIMESTER III - Asi, Melania; Arsulfa; Heyrani; Resyana, Hesti; Malahayati, Andi (Poltekkes Kemenkes Kendari, 2024)
Background: Labor pain can cause stress that leads to excessive release of hormones such as catecholamines and steroids, these hormones can cause smooth muscle tension and vasoconstriction of the uterus, decrease the circulation of the uteroplacenta, blood flow and oxygen to the uterus, and cause uterine ischemia which makes the impulse increase. The non-pharmacological method used to reduce pain and accelerate head lowering is pelvic rocking gymnastics using a gym ball where sitting straight on the ball, the earth's gravitational force will help the bottom of the fetus descend to the pelvis so that labor becomes shorter. The importance of the application of gymnastics is so that it is necessary to provide information and health education about pelvic rocking gymnastics that can train pregnant women. Objective: to improve the knowledge and ability of pelvic rocking gymnastics. Method: the target of the activity is pregnant women in the third trimester in Bajoe Village. This activity was carried out for 1 month with two meetings where at the first meeting education and simulation of pelvic rocking gymnastics were given, then at the second meeting, two weeks after the first meeting, an evaluation of the understanding of the participants was carried out. Conclusion: the results of this activity can increase the mother's knowledge and ability to do pelvic rocking gymnastics.